2023
DOI: 10.5194/acp-23-3233-2023
|View full text |Cite
|
Sign up to set email alerts
|

Unambiguous identification of N-containing oxygenated organic molecules using a chemical-ionization Orbitrap (CI-Orbitrap) in an eastern Chinese megacity

Abstract: Abstract. Oxygenated organic molecules (OOMs) are dominated by the N-containing species in polluted urban environments. As N-containing OOMs, especially those with more than one nitrogen atom, prevail in the high m/z (mass-to-charge) range (m/z> 350 Th), unambiguous identification of N-containing OOMs is highly desirable for understanding of their formation processes, precursors and influencing factors. To achieve this, we applied an ultra-high-resolution chemical-ionization Orbitrap (CI-Orbitrap) in a fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
2
1
0
Order By: Relevance
“…The workflow, based on current knowledge of VOC oxidation using the measured molecular composition, enabled us to assign these O x N compounds to their likely VOC precursor classes, corresponding to aliphatic-O x N, aromatic-O x N, isoprene-O x N, and monoterpene-O x N (Figure a). Overall, the main categories are remarkably similar throughout the haze event, with the O x N compounds predominantly originating from anthropogenic sources (89–96%), which is in agreement with several recent works conducted in other Chinese places, such as Beijing, Shanghai. ,, …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The workflow, based on current knowledge of VOC oxidation using the measured molecular composition, enabled us to assign these O x N compounds to their likely VOC precursor classes, corresponding to aliphatic-O x N, aromatic-O x N, isoprene-O x N, and monoterpene-O x N (Figure a). Overall, the main categories are remarkably similar throughout the haze event, with the O x N compounds predominantly originating from anthropogenic sources (89–96%), which is in agreement with several recent works conducted in other Chinese places, such as Beijing, Shanghai. ,, …”
Section: Resultssupporting
confidence: 90%
“…Overall, the main categories are remarkably similar throughout the haze event, with the OxN compounds predominantly originating from anthropogenic sources (89−96%), which is in agreement with several recent works conducted in other Chinese places, such as Beijing, Shanghai. 15,27,68 As shown in Figure 2a, the aromatic-OxN accounted for 88 ± 2.5% of the total oxidized-N abundance, which was a comparable previous observation result obtained in the urban atmosphere of Northern China. 25,69 Although the oxidation pathways and molecular composition of some aromatic VOCderived products have been reported in previous studies, 70,71 the known aromatic-CHON species were relatively scarce and could only account for 0.2−0.6‰ of total OM mass reported by a recent field observation.…”
Section: Sources Of Oxidized-n Compoundssupporting
confidence: 89%
“…For instance, organic nitrates, formed as a product of reactions between organic peroxy radicals and nitric oxide, as well as alkenes with the nitrate radical, represent a notable fraction of OA mass at multiple sites, according to aerosol mass spectrometer (AMS) measurements (Kiendler‐Scharr et al., 2016; Xu et al., 2021). Recent studies have suggested that nitrogenous molecules dominate the condensing anthropogenic organic vapors over China's megacities, indicating the potentially abundant contribution of OA N to SOA mass in the urban atmosphere (Lu et al., 2023; Nie et al., 2022). Third, nitroaromatic compounds, derived from primary emissions such as biomass burning and secondary formation between phenols and NO x , are critical light‐absorbing aerosols (Lin et al., 2017; Palm et al., 2020).…”
Section: Introductionmentioning
confidence: 99%